Improving Fertilization Efficiency through Biochar Application and the Development of Superior Varieties of Red Chili Peppers - Permana, Indra; Intan Nurcahya; Abdul Hakim; Romy Faisal Mustofa; Dewi, Tirta Kumala (Jurnal Biologi Tropis, 2024)
Soil quality improvement can be achieved through the application of soil ameliorants such as Biochar. Developing superior varieties that are efficient in fertilization is also an effort to reduce the use of chemical fertilizers. This study aims to improve fertilization efficiency through the application of Biochar and the development of hybrid large red chili varieties at Siliwangi University. The research method used a Split-split plot design, consisting of large red chili varieties as the main plot, Biochar dosage treatment as the sub-plot, and different doses of inorganic fertilizers as the sub-sub plot. The main plot treatment consisted of four levels: Baja Variety (V1), UNSIL-01 (V2), UNSIL-02 (V3), and UNSIL-03 (V4). The sub-plot had two levels: without Biochar (B0) and 10 tons/ha of Biochar (B1). The inorganic fertilizer treatment consisted of three levels: 25% (P1), 50% (P2), and 75% (P3) of the standard dose. Each treatment was repeated three times, resulting in 72 research plots. The slow pyrolysis of coconut shell produced biochar with an average efficiency of 33.7% based on the dry weight of the feedstock. Optimal pyrolysis conditions, with temperatures ranging between 275°C and 485°C over 6 to 9 hours. Among the tested chili varieties, UNSIL-03 (V4) and Baja (V1) showed the highest growth performance, particularly in height and stem diameter, in biochar-amended soil. The application of 25% of the standard inorganic fertilizer dose, in combination with biochar, was sufficient to achieve optimal plant growth across most varieties, especially Baja (V1) and UNSIL-03 (V4).